Prognostic Value of the Lung Immune Prognostic Index May Differ in Patients Treated With Immune Checkpoint Inhibitor Monotherapy or Combined With Chemotherapy for Non-small Cell Lung Cancer - Wang, Wenxian; Huang, Zhangzhou; Yu, Zongyang; Zhuang, Wu; Zheng, Weijun; Cai, Zhijian; Shi, Lei; Yu, Xinmin; Lou, Guangyuan; Hong, Wei; Zhang, Yiping; Chen, Ming; et al. (Frontiers in Oncology, 2020)
Background: Lung immune prognostic index (LIPI) status was recently developed to predict responses to immune checkpoint inhibitor (ICI) treatments. However, it is unclear whether LIPI is a prognostic index both for patients treated with ICI monotherapy and ICIs combined with chemotherapy (ICIs CC). Methods: This retrospective study established the patterns of LIPI in Chinese patients with advanced non-small cell lung cancer (NSCLC). LIPI based on the derived neutrophil-to-lymphocyte ratio greater than 3 and lactate dehydrogenase greater than the upper limit of normal was developed to characterize good, intermediate or poor LIPI status. Associations between LIPI status and progression-free survival (PFS), and overall survival (OS) were analyzed. Kaplan-Meier curves and Cox proportional hazards models were used to determine survival differences. Results: Three hundred and thirty patients were included in this study. Of these patients, 216 received ICI monotherapy and 114 received ICIs CC. A good LIPI status was associated with better progression-free survival (PFS) (6.1 months vs. 2.3 months vs. 2.1 months, P = 0.023) and overall survival (OS) (24.2 months vs. 14.5 months vs. 9.3 months, P < 0.001) in ICI monotherapy compared to intermediate or poor LIPI status. No differences in PFS (17.9 vs. 9.9 months vs. 7.6 months, P = 0.355, respectively) and OS (P = 0.346) were observed in patients who received ICIs CC. Moreover, we found that patients who had an improved LIPI status compared with the baseline value had a longer PFS with ICI monotherapy and LIPI intermediate status (8.4 months vs. 2.1 months vs. 1.4 months, P < 0.001). However, in patients treated with ICIs CC, these dynamic changes were not observed (P=0.444). Conclusions: LIPI status and dynamic changes in LIPI could be prognostic markers of treatment response to ICI monotherapy, but not to ICIs CC. In particular, good LIPI status was associated with a better clinical outcome compared with intermediate and low LIPI status in ICI monotherapy treatment.